2011
DOI: 10.1007/s13105-011-0114-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant erythropoietin on ischemia–reperfusion-induced apoptosis in rat liver

Abstract: Ischemia-reperfusion (I/R) cannot be avoided in liver transplantation procedures, and apoptosis is a central mechanism of cell death after liver reperfusion. Protective effect of recombinant erythropoietin (rhEPO) on liver apoptosis has not been clearly investigated. This work investigated intraportal (IP) rhEPO-protective effect in a rat model of hepatic I/R-induced apoptosis and its appropriated time and dose of administration. Eight groups were included (n = 10/group): sham-operated, I/R (45 min ischemia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Pre-treatment with rhEPO has been shown to ameliorate hepatic IR injury; inhibition of apoptosis has been cited as a primary mechanism of this protection[23]. Warm hepatic IR leads to necrotic cell death (oncosis), and often occurs within minutes of reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-treatment with rhEPO has been shown to ameliorate hepatic IR injury; inhibition of apoptosis has been cited as a primary mechanism of this protection[23]. Warm hepatic IR leads to necrotic cell death (oncosis), and often occurs within minutes of reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms responsible for ischemic PostC of the liver are not fully understood, some studies have shown that the two processes have many similarities [6][7][8]. Recent studies have demonstrated that some agents, such as adenosine A2A receptor agonist [8], rhEPO [9], and sevoflurane [10], can be used as pharmacological inducers of PostC as well as PreC. Milrinone has been shown to have PreC properties using an orthotopic liver transplantation model and warm IR injury model in rats [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies have demonstrated that some agents, such as adenosine A2A receptor agonist [8], recombinant erythropoietin (rhEPO) [9], and the volatile anesthetic sevoflurane [10], can be used as pharmacological inducers of PostC as well as PreC.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Shawky et al investigated the effect of intraportal recombinant human erythropoietin (rhEPO) in a rat model of hepatic IR injury as well as its appropriate time and dose of administration [ 64 ]. Moreover, they compared preconditioning with rhEPO (24 h or 30 min before ischemia) with postconditioning with rhEPO (administering it at reperfusion).…”
Section: Pharmacological Postconditioningmentioning
confidence: 99%